Electromagnetic Wave Scattering by Small Impedance Particles of an Arbitrary Shape and Applications - Ramm, Alexander G. (Multidisciplinary Digital Publishing Institute, 2014)
The proposal deals with electromagnetic (EM) wave scattering by one and many small impedance particles of an arbitrary shape. Analytic formula is derived for EM wave scattering by one small impedance particle of an arbitrary shape and an integral equation for the effective field in the medium where many such particles are embedded. These results are applied for creating a medium with a desired refraction coefficient. The proposed theory has no analogs in the literature. (Mathematical Subject Classification: 35J05, 35J25, 65N12, 78A25, 78A48.)
Keywords: Electromagnetic wave scattering; Small impedance particles; Many-body scattering problem; Refraction coefficient; Permeability; Creating materials with a desired refraction coefficient